16 Characterization of an optical dosimeter fiber for radiotherapy use. (December 2018) - Allegrini, O.; Amblard, R.; Villeneuve, R.; Garnier, N.; Serrano, B.
Abstract : Introduction: Optical dosimeter fiber (FOD) with small dimension and promising scintillation properties are investigated in radiotherapy especially in small field. We propose to study FOD dosimetric characteristic towards its answer on small fixed 3 × 3 cm 2 beams of a Varian linear accelerator with flattening-filter-free (FFF) option. Methods: The measurements were performed by TrueBeam-Novalis with 6 MV, 15 MV, 6 MVFFF and 10 MVFFF photon beams, dose rate varied up to 600 MU/min for two first beams and up to 1400 and 2400 MU/min for others. The inorganic scintillator has an emission at approximately 620 nm (DoseVue NV). The hemispherical detector was fixed on a 1 mm diameter optical fiber to guide the light to a photodetector. Signal is converted in relative dose toward DoseWire™ system. We studied repeatability, reproducibility, linearity and dose rate response using slab solid water and 0.125 cc reference ionization chamber (IC) (PTW). StereoPHAN™ (Sun Nuclear) phantom was used for radial FOD angular response. The results are expressed as [(2 ∗ StandardDeviation)/Mean] ∗ 100. Results: The excellent repeatability, for 20 measurements, of 6 MV, 6 MVFFF, 10 MVFFF and 15 MV beams were respectively 0.18%, 0.19%, 0.14% and 0.12% for FOD and 0.06%, 0.04%, 0.14% and 0.07% for IC. The reproducibility, for 10 measurements, were 5.5% (FOD) and 1.3% (IC). The relative dose/UM linearity between 5 and 10000 UM for the 6 MV, 6 MVFFF, 15 MVFFF and 15 MV were respectively 1.1%, 0.7%, 1% and 1.2% (FOD) and 0.6%, 0.2%, 0.14% and 0.2% (IC). The dose rate answer for 6, 15 MV and 6, 10 MVFFF were respectively 0.3%, 0.27% and 0.5%, 0.6% (FOD), 0.3%, 0.1% and 0.1%, 0.15% (IC). The FOD angular response was 1.2%. Conclusion: All similar results of FOD in comparison of reference 0.125 cc IC for the repeatability, dose linearity and does rate make this scintillator a good relative detector. The isotropic and small size scintillator have promising relative dosimetry applications in small fields.